Association between the geriatric nutritional risk index and the risk of stroke in elderly patients with hypertension: A longitudinal and cohort study - Cai, Xintian; Hu, Junli; Wen, Wen; Wang, Mengru; Zhu, Qing; Liu, Shasha; Yang, Wenbo; Dang, Yujie; Hong, Jing; Li, Nanfang (Frontiers in Nutrition, 2022)
Objective: We aimed to investigate the association between the GNRI and the risk of stroke in elderly patients with hypertension. Methods: A total of 5312 elderly hypertensive patients free of history of stroke were included. Multivariate Cox models were used to calculate hazard ratios (HRs) and their 95% confidence intervals (CIs) for stroke and its subtypes. Results: The average time of follow-up was 3.8 years, and the median time was 3.2 years. We identified 640 individuals with stroke, of whom 526 had an ischemic stroke (IS) and 114 had a hemorrhagic stroke (HS). After adjusting for confounding variables, compared with participants in the lowest quartile of the GNRI, those in the third and fourth quartiles were associated with a decreased risk of stroke (adjusted HR 0.72, 95% CI 0.58-0.90, and adjusted HR 0.58, 95% CI 0.46-0.74, respectively, P for trend < 0.001). Similar results were found for IS and HS. Moreover, there were L-shaped associations of GNRI with new-onset HS (P for nonlinearity = 0.034). Multiple sensitivity analyses and stratified analyses did not materially change the results. Conclusions: In summary, we found that a lower GNRI was associated with a higher risk of incident stroke in elderly hypertensive patients. Additional prospective data collection is required to confirm our findings.